الأبعاد الدلالية للأناشيد الموجهة لمتعليمي السنة الخامسة ابتدائي دراسة تحليلية ميدانية - فيروز حشيفة; هاجر شيباني (University of Eloued جامعة الوادي, 2025)
يهدف هذا البحث إلى دراسة الأبعاد الدلالية الكامنة في الأناشيد التعليمية الموجهة لمتعلمي السنة الخامسة من التعليم الأساسي، من خلال تحليل محتواها النصي ورصد أثرها التربوي والمعرفي والنفسي. ينطلق البحث من فرضية أن الأناشيد، بما تحمله من تراكيب لغوية وصور بلاغية، تشكل وسيلة فعالة لتعزيز المهارات اللغوية والقيم الاجتماعية، وترسيخ المفاهيم الوطنية والإنسانية لدى المتعلمين. يعتمد التحليل على مقاربة دلالية تستند إلى تصنيف الأبعاد إلى أربعة محاور رئيسية: البعد اللغوي، والبعد القيمي (الأخلاقي والاجتماعي)، والبعد النفسي-الوجداني، والبعد المعرفي-التثقيفي. وقد خلصت الدراسة إلى أن الأناشيد توظف عناصر لغوية بسيطة لكنها غنية بالصور الجمالية والرموز التي تناسب مستوى المتعلمين، وتسهم في إثراء رصيدهم اللغوي وتعزيز قدرتهم على التعبير. كما أظهرت الأناشيد حضورًا قويًا للقيم الإيجابية مثل التعاون، حب الوطن، احترام الآخر، والعمل الجاد، ما يعكس توجهًا تربويًا واضحًا. أما من الناحية النفسية، فتبين أن الأناشيد تساهم في دعم الصحة النفسية للمتعلم من خلال إيقاعاتها المحببة ورسائلها الإيجابية، مما يعزز الشعور بالانتماء والطمأنينة. على الصعيد المعرفي، تتضمن الأناشيد مضامين تثقيفية توسع مدارك المتعلمين في مجالات متنوعة مثل الطبيعة، التاريخ، والمجتمع. خلص البحث إلى أهمية إدماج الأناشيد ضمن المناهج التعليمية بشكل منهجي ومدروس، مع توصية بضرورة تطوير محتواها ليواكب تطورات المجتمع ويعكس اهتمامات الجيل الجديد، مؤكدًا على دورها المحوري في بناء شخصية المتعلم المتوازنة. This study aims to examine the semantic dimensions embedded in educational songs directed at fifth-year primary learners by analyzing their textual content and assessing their educational, cognitive, and psychological impact. The research is based on the hypothesis that songs, through their linguistic structures and figurative imagery, serve as an effective tool to enhance language skills, instill social values, and reinforce national and human concepts among learners. The analysis adopts a semantic approach categorized into four main axes: the linguistic dimension, the value-based dimension (ethical and social), the psychological-emotional dimension, and the cognitive-educational dimension. The study found that the songs employ simple linguistic elements enriched with aesthetic imagery and symbols suitable for the learners’ level, contributing to vocabulary enrichment and improved expressive ability. The songs also prominently feature positive values such as cooperation, patriotism, respect for others, and diligence, reflecting a clear educational orientation. Psychologically, the findings indicate that songs support learners' mental well-being through their engaging rhythms and positive messages, fostering a sense of belonging and reassurance. On the cognitive level, the songs include educational content that broadens learners’ horizons in various fields such as nature, history, and society. The research concludes by emphasizing the importance of integrating songs systematically into educational curricula, recommending the continuous development of their content to keep pace with societal changes and reflect the interests of the new generation, highlighting their crucial role in shaping a well-balanced learner’s personality.
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: الأناشيد، الدلالة، الأبعاد الدلالية; hymns; meaning; semantic dimensions